2021
DOI: 10.3389/fimmu.2021.683330
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Profiling Reveals Transcriptional Signatures and Cell-Cell Crosstalk in Anti-PLA2R Positive Idiopathic Membranous Nephropathy Patients

Abstract: Idiopathic membranous nephropathy (IMN) is an organ-specific autoimmune disease of the kidney glomerulus. It may gradually progress to end-stage renal disease (ESRD) characterized by increased proteinuria, which leads to serious consequences. Although substantial advances have been made in the understanding of the molecular bases of IMN in the last 10 years, certain questions remain largely unanswered. To define the transcriptomic landscape at single-cell resolution, we analyzed kidney samples from 6 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 70 publications
2
30
1
Order By: Relevance
“…Furthermore, the frequency of glycosuria was only 6% in glomerulonephritis [ 17 ]. Tubular injury and the crosstalk between tubular cells and other cells are important processes in the progression of chronic kidney disease [ 18 , 19 ]. Most AKI manifested with the acute renal tubular injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the frequency of glycosuria was only 6% in glomerulonephritis [ 17 ]. Tubular injury and the crosstalk between tubular cells and other cells are important processes in the progression of chronic kidney disease [ 18 , 19 ]. Most AKI manifested with the acute renal tubular injury.…”
Section: Discussionmentioning
confidence: 99%
“…Albumin overload could indeed induce renal tubular injury [ 24 ]. A recent research with single cell sequence also showed that proximal tubular cells had higher TNF signaling pathway, IL-17 signaling pathway, NOD like receptor, and apoptosis expression in massive proteinuria patients than nonmassive proteinuria patients [ 19 ]. Thus, it would be of importance to discriminate the tubular injury when patients had massive proteinuria.…”
Section: Discussionmentioning
confidence: 99%
“…sPLA2-IB can promote podocyte injury by downregulating autophagy by activating the p38 MAPK/mTOR/ULK1 (Ser757) pathway [ 28 ]. Single-cell sequencing analysis of renal tissue from healthy individuals and PLA2R-positive IMN patients revealed that differentially expressed genes in renal parenchymal cells lead to MN through pathways such as MAPK [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The extracted fresh kidney tissue samples were processed and dissociated into single-cell suspensions using a previously described method (18).…”
Section: Single-cell Suspension Preparationmentioning
confidence: 99%
“…Since the Humphreys group adopted scRNA-seq in healthy adult kidneys and one kidney transplant biopsy, there have been many advances in singlecell sequencing technology in mapping the human kidney transcriptome (16). Recently, we have taken advantage of this technique to generate renal atlases in IgA nephropathy (17) and membranous nephropathy (18).…”
Section: Introductionmentioning
confidence: 99%